Significado nao ansioso dos fatores “Luminosidade” na provade Rorshach - Silveira, Anibal (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
We call “light values” those responses which pick up tone gradations of the inkblot, in the monotone or in the color plates. By selecting such “light” association, the subject may follow the rules met within the average adult, therefore with an objective mind, or disclose quite subjective trends. One must consider, therefore, discrete determining factors to describe this process, which gives rise to a scale comparable to that devised by Binder.